Case report: multiple UGT1A1 gene variants in a patient with Crigler-Najjar syndrome - Gailite, Linda (BMC Pediatr, 2018)
BACKGROUND: Inherited unconjugated hyperbilirubinemia is caused by variants in the gene UGT1A1 leading to Gilbert’s syndrome and Crigler-Najjar syndrome types I and II. These syndromes are differentiated on the basis of UGT1A1 residual enzymatic activity and its affected bilirubin levels and responsiveness to phenobarbital treatment. CASE PRESENTATION: In this report, we present a boy with Crigler-Najjar syndrome type II with high unconjugated bilirubin levels that decreased after phenobarbital treatment but increased in adolescence. Four different UGT1A1 gene variants have been identified for this patient, of which one is novel (g.11895_11898del) most likely confirming diagnose molecularly. CONCLUSIONS: The presented case highlights the challenges encountered with the interpretation of molecular data upon identification of multiple variants in one gene that are causing different degree reducing effect on enzyme activity leading to several clinical conditions.